Investigation of Glass-to-Concrete Adhesive Joints through 3-Point Bending Tests - Cas Maertens; Bert Van Lancker; Alessandro Proia; Roman Wan-Wendner; Jan Belis (Challenging Glass Conference Proceedings, 2024)
This study aims to explore innovative structural applications involving the bonding of glass to concrete. To date, academic literature has provided limited insights into the adhesive bonding between glass and concrete. Our investigation focuses on understanding the bond behaviour of glass-concrete joints through small-scale three-point bending tests. We analyse how variations in the adhesive joint configuration and the selection of adhesives impact the bond behaviour. By systematically examining these factors, we aim to provide valuable insights into optimising the design and construction of bonded glass-concrete elements. These insights serve as the foundation for future studies, exploring innovative applications where structural considerations seamlessly merge with aesthetic, durability, and safety considerations. The ultimate objective is to evaluate the potential of glass bonded to concrete, aiming to not only excel in structural performance but also to meet multifaceted demands across diverse engineering applications.